Soccer transition training. Moving between attack and defense - Englund, T.; Pascarella, J. (Meyer & Meyer Sport (UK) Ltd., 2019)
The 2018 soccer World Cup highlighted the increasing emphasis on transitional awareness and tactics. From elite domestic leagues worldwide to local youth coaching clinics, there is a pronounced effort to help coaches and players recognize and seize the advantages gleaned through controlling transitional moments during a match. Pep Guardiola (Manchester City), Jürgen Klopp (Liverpool), and Mauricio Pochettino (Tottenham Hotspurs), among many others, have climbed to forefront of the coaching ranks in recent years, espousing various pressing, counter-pressing, and counterattacking schemes that have made their teams so difficult to play against. Though coaches worldwide have focused on transitional moments as the next tactical revolution in soccer, there has been a remarkable lack of written coaching material on the subject. Soccer Transition Training is the first complete study of critical transition moments in the beautiful game. This book offers everything coaches at any level need to help their teams dominate in transition Written by two leading soccer educators with decades of experience coaching at the highest levels from youth to professional, Soccer Transition Training is the book that soccer coaches have been waiting for, both as a discussion of the nature of transition in the ever-evolving game and as a teaching tool to help their teams dominate on both sides of the ball! Klappentext